For the equation to be equal, the argument of the logarithms on both sides of the equation must be equal.

Move all terms containing <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> to the left side of the equation.

Subtract <math><mstyle displaystyle="true"><mn>2</mn><mi>x</mi></mstyle></math> from both sides of the equation.

Subtract <math><mstyle displaystyle="true"><mn>2</mn><mi>x</mi></mstyle></math> from <math><mstyle displaystyle="true"><mo>-</mo><mn>2</mn><mi>x</mi></mstyle></math> .

Move all terms not containing <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> to the right side of the equation.

Subtract <math><mstyle displaystyle="true"><mn>7</mn></mstyle></math> from both sides of the equation.

Subtract <math><mstyle displaystyle="true"><mn>7</mn></mstyle></math> from <math><mstyle displaystyle="true"><mo>-</mo><mn>1</mn></mstyle></math> .

Divide each term by <math><mstyle displaystyle="true"><mo>-</mo><mn>4</mn></mstyle></math> and simplify.

Divide each term in <math><mstyle displaystyle="true"><mo>-</mo><mn>4</mn><mi>x</mi><mo>=</mo><mo>-</mo><mn>8</mn></mstyle></math> by <math><mstyle displaystyle="true"><mo>-</mo><mn>4</mn></mstyle></math> .

Cancel the common factor of <math><mstyle displaystyle="true"><mo>-</mo><mn>4</mn></mstyle></math> .

Cancel the common factor.

Divide <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> by <math><mstyle displaystyle="true"><mn>1</mn></mstyle></math> .

Divide <math><mstyle displaystyle="true"><mo>-</mo><mn>8</mn></mstyle></math> by <math><mstyle displaystyle="true"><mo>-</mo><mn>4</mn></mstyle></math> .

Do you know how to Solve for x log base 20 of -2x+7 = log base 20 of 2x-1? If not, you can write to our math experts in our application. The best solution for your task you can find above on this page.